The Classical Detective Story Formula from Literature to Videogames - Silva Ramos, Elisa (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2021: Anais Estendidos do XX Simpósio Brasileiro de Jogos e Entretenimento Digital, 2021)
The classical detective story format, originated from Edgar Allan Poe’s tales of ratiocination, has spread into all kinds of different media over the past century, transforming itself each time to make better use of each medium’s specificities. This paper stems from John Cawelti's studies about the literary formula of the detective narrative, using them as a base to analyze E. A. Poe's short story “Murders in the Rue Morgue” and Lucas Pope’s videogame Return of the Obra Dinn. I seek to understand how the literary conventions of the genre were adapted, transposed and recreated in the interactive medium. Through Cawelti’s framework for the classical detective story formula, the analysis focuses on four main patterns found in the genre: (1) situation, (2) action, (3) characters and relationships and (4) setting. I will argue here that the element of interaction is responsible for modifying the most important component of the literary genre: the detective figure. This important change alters the purpose of the detective story genre itself; however, it also makes for an experience which is more on par with the literary detective’s actions as well.